RANCANG BANGUN SISTEM PAKAR PENANGGULANGAN PENYAKIT KEDELAI - Astuti, Indah Puji; Hermadi, Irman; Buono, Agus; Mutaqin, Kikin H (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Early detection and identification of soybean diseases is important to support better productivity of soybean. The demand for the availability of an expert on soybean disease is very high, especially for the beginners in the field of agriculture. However, the number and time allocation of the experts are not adequate to serve farmers located in different geographical areas. Therefore, an expert system is proposed as a solution to use as a diagnostic tool for soybean diseases just like a human expert. It will be even easier when the system is implemented into an Android-based application to be used anywhere and anytime. The objective of this study was to analyze and design an expert system for early identification of soybean diseases. This study was adopting the Expert System Development Life Cycle (ESDLC) approach. The stages were project initialization, knowledge engineering process, and implementation. The study was started with the project initialization phase that conducted in September 2014 and the completion of the implementationphase in August 2015. The results of research were in the form of document analysis and prototype system.